Analysis of the Trading Margin of Micro Scale Tempe Processing Business in South Konawe Regency - Dhian Herdhiansyah; Nasrullah Nasrullah; La Rianda; Asriani Asriani (JURNAL AGROINDUSTRI HALAL, 2021)
This study aims to analyze the trading margin of tempe processing business a micro-scale in the South Konawe Regency. The Determination of the location of the study was done deliberately (purposive sampling). The sampling method used in this research is the census method technique, in which the sample used in this study is the tempe business Micro A, Micro B, Micro C, Micro D, Micro E, and Mikro F, documents and literature. The analysis used is the trading system margin analysis. The results showed that the comparison of prices in each chain actor, the highest business margin of micro-scale tempe business was tempe F with the trading margin of collector traders by 24%, collectors to market traders 26.47%.